Preparation and in vitro characterization of electrospun scaffolds composed of chitosan, gelatin and 58S bioactive glass nanoparticles for skin tissue engineering - Nosrati, Hamed; Banitalebi-Dhkordi, Mehdi; Khodaei, Mohammad; Sharifi, Esmaeel; Asadpour, Shiva; Mansouri, Kamran; Soleimannejad, Mostafa (Journal of Shahrekord University of Medical Sciences, 2022)
Background and aims: The presence of an appropriate scaffold at the wound site could significantly improve the healing process. In this study, we aimed to prepare a biomimetic nanocomposite scaffold composed of chitosan, gelatin, and 58S bioglass nanoparticles for skin tissue engineering. Methods: The nanocomposite scaffolds composed of chitosan, gelatin, and 58S bioglass nanoparticles were fabricated through electrospinning process. Then the cell viability assay was performed in order to evaluate the biological properties of the membranes. The optimum concentration of bioglass nanoparticles was determined for further studies. In vitro characterization was also performed to evaluate physicochemical properties of the scaffolds. Results: The chitosan/gelatin scaffold containing 2% of 58S bioglass nanoparticles showed no cell toxicity, and the dermal fibroblasts were found capable of proliferation on the membrane. The in vitro results obtained from the scanning electron microscopy (SEM), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), and porosity tests demonstrated the appropriate properties of the membrane as a scaffold for skin regeneration. Conclusions: It was concluded that a chitosan-gelatin membrane containing 2% of 58S bioglass nanoparticles had the potential to function as a scaffold to accelerate wound healing due to its suitable properties, such as high porosity, high surface/volume ratio, and excellent biocompatibility.